CHET TILIDA KOMMUNIKATIV KOMPETENSIYANING MAZMUNI VA TUZILISHI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article presents different views on communicative competence and its types, described in domestic and foreign literature. In addition, a description is given of linguoprofessional competence (LPC) and the types of models for its formation.
Keywords: communicative training, communicative competence, competence, specification, foreign language projects, sociolinguistic competence, social competence, linguodidactics, sociocultural competence, strategic competence, lexical units, discursive competence.